2013
DOI: 10.1002/pc.22490
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of modified sodium lignosulfonate hydrogel–silver nanocomposites

Abstract: In this article, modified sodium lignosulfonate (MSLS) hydrogel particles were prepared using sodium lignosulfonate as starting material. The hydrogel particles exhibit a reversible property transformed between the two states of macrohydrogel and microhydrogel by ultrasonic dispersion and vacuum drying. Using this property, highly stable and uniformly dispersed silver nanoparticles (AgNPs) have been prepared via in situ reduction of silver ions (silver nitrate) in the microhydrogel aqueous dispersion with sodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
1
6
0
1
Order By: Relevance
“…This phenomenon shows that heterogenous nucleation, which needs a higher temperature, was occurred in PZ. This similar effect has been previously reported 44 , which indicated that ZnO particles were acted as nucleation agents to guide the crystallization of PPR to a higher temperature. Surely, ZnO particles still had the ability to induce heterogenous nucleation and crystallization in PVZ3.…”
Section: Crystallization Behaviorssupporting
confidence: 88%
See 1 more Smart Citation
“…This phenomenon shows that heterogenous nucleation, which needs a higher temperature, was occurred in PZ. This similar effect has been previously reported 44 , which indicated that ZnO particles were acted as nucleation agents to guide the crystallization of PPR to a higher temperature. Surely, ZnO particles still had the ability to induce heterogenous nucleation and crystallization in PVZ3.…”
Section: Crystallization Behaviorssupporting
confidence: 88%
“…where ΔH m and ΔH c are the enthalpies of melting and cold crystallization during heating, respectively; ΔH m 0 is the enthalpy assuming 100% crystalline PPR homopolymer (209 J/g); 14,44 and Φ is the weight fraction of PPR component in the sample. It should be noted that all samples have no cold crystallization peak, so the ΔH c value is 0.…”
Section: Analysis Of Crystallizationmentioning
confidence: 99%
“…31 The -CH 2 (2920 cm À1 ), -C]C-(1560 cm À1 ), aromatic ring (1508 cm À1 ), C-H (1458 cm À1 ) group, and C-O (1120 cm À1 ) were present in the spectra of SLS-Ti 3 C 2 . 14,32 Lignin sulfonic is an amphoteric hydrophilic polymer surfactant with both carbon chains, phenolic hydroxyl hydrophobic group and hydrophilic group of sulfonic acid. Under the effect of van der Waals forces and steric hindrance effects, the hydrophobic group improved the dispersion of Ti 3 C 2 T x MXenes in water, and the hydrophilic group stretched in the aqueous solution and provided a nucleation channel for the in situ coated and intercalated NiZn ferrite.…”
Section: Resultsmentioning
confidence: 99%
“…Some literatures report that the introduction of nanoparticles can reduce the domain size of the dispersed phase and improve the compatibility of the blends. [ 24–27 ] Especially, Yu et al. [ 24 ] found that the hydrophobic silica can improve the interfacial adhesion between poly(lactic acid) (PLA) and TPU through hydrogen bonding.…”
Section: Resultsmentioning
confidence: 99%